ANTIBACTERIAL AND ANTIBIOFILM ACTIVITIES OF TRANS-CINNAMALDEHYDE NANOEMULSION AGAINST ESCHERICHIA COLI - L RAJ, UTKRISHTA; GAUTAM, MEGHA; DANG, SHWETA; GABRANI, REEMA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Trans-cinnamaldehyde (TC) has shown antimicrobial activity against various microorganisms, but its direct use has some disadvantages such as skin irritation, low bioavailability, and low solubility. The objective of the present work was to develop the oil-in-water nanoemulsions (NEs) of TC to enhance its antimicrobial activity against Escherichia coli. Methods: The NEs of TC were prepared using triton x-100 and isopropyl alcohol as surfactant and cosurfactant. The developed NE was studied for size, zeta potential, and stability. NEs were evaluated for antimicrobial and antibiofilm activity against E. coli as indicator organism. NEs possible mode of action on E. coli was assessed by scanning electron microscopy (SEM). Results: Stable NEs of TC exhibited a particle size of 210 nm and were able to inhibit the growth of planktonic as well as biofilm cultures of E. coli at 67 μg/ml. The ruthenium red staining indicated the inhibition of glycoprotein layer formation in extracellular matrix after treating with NE. TC-NE exhibited substantial decrease in E. coli growth as well as its viability at its minimum inhibitory concentration as determined by 3-(4,5-dimethylthiazol- 2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The mode of action of cinnamaldehyde through β-galactosidase assay on E. coli ML-35p strain indicated that it altered the bacterial cell membrane permeability. SEM results showed the presence of holes on the cell wall of the E. coli in the presence of TC-NE. Conclusions: TC-NEs exhibited enhanced antimicrobial activity and were effective against E. coli biofilm. They also exhibited microbicidal activity and altered E. coli membrane permeability.